ANALISIS PENGARUH MEMBER CARD, CUSTOMER REWARD PROGRAM, DAN SERVICE QUALITY, TERHADAP CUSTOMER LOYALTY DENGAN CUSTOMER SATISFACTION SEBAGAI VARIABEL MODERASI - David Christian; Hendy Tannady (Journal of Economic, Bussines and Accounting (COSTING), 2026)
Retail companies are required not only to attract new customers but also to strengthen customer engagement through innovative marketing strategies such as the implementation of member cards, customer reward programs, and improvements in service quality and customer satisfaction. Member card programs provide added value in the form of discounts, gifts, and exclusive services, thereby encouraging customer loyalty. Meanwhile, customer reward programs serve as incentives to retain customers in the long term. In addition, service quality and customer satisfaction are key determinants in building customer loyalty, which is reflected not only through repeat purchases but also through customers’ willingness to recommend the brand to others.This study aims to analyze the influence of member cards, customer reward programs, and service quality on customer loyalty in plastic retail companies, both partially and simultaneously, with customer satisfaction functioning as a moderating variable. The findings indicate that member cards, customer reward programs, and service quality each have a positive effect on customer loyalty. Furthermore, customer satisfaction strengthens the relationship between member card usage, customer reward programs, service quality, and customer loyalty.